Firm Performance and Modes of Innovation - Nunes, S. (2014)
It has been shown that firms tend to develop different modes of innovation, based on the relationship between the different types of underlying knowledge and learning processes. This paper seeks to identify different modes of business innovation, relating them to firms’ innovative and economic performance, and to analyze the relationship between the different innovation modes and the economic impact of the crisis on firms’ performance. These hypotheses are tested by regression and latent class models for the Portuguese population of firms, using a sample of 397 firms, classified according to technological intensity, firm size and region. Our results show three different modes of innovation in terms of the relationship between economic and innovative performance, with significant differences in terms of resilience in the face of the economic crisis. These findings lead to a reflection on innovation, competitiveness and regional policy.